2021
DOI: 10.1136/bmjopen-2021-050289
|View full text |Cite
|
Sign up to set email alerts
|

Oral health assessment of older adults living in long-term care facilities by non-dental professionals: a systematic review protocol of instruments

Abstract: IntroductionRegular oral health assessment among older adults living in long-term care facilities (LTCF) can improve their oral health. Different instruments have been developed and used to evaluate the oral health of institutionalised older people by non-dental professionals. These instruments must demonstrate adequate measurement properties. This systematic review aims to examine the studies describing the instruments employed to assess the oral health of older adults living in LTCF by non-dental professiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…This systematic review was developed and reported according to the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) 11 and COSMIN checklist for systematic reviews 12 . The protocol of this systematic review was registered on the PROSPERO database (Ref: CRD42020191479) and previously described 13 …”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…This systematic review was developed and reported according to the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) 11 and COSMIN checklist for systematic reviews 12 . The protocol of this systematic review was registered on the PROSPERO database (Ref: CRD42020191479) and previously described 13 …”
Section: Methodsmentioning
confidence: 99%
“…A third reviewer was consulted in case of disagreements. Detailed information on the methods is found in other publications 13 …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations